Social Capital Relationship with Mustard Greens Farmers’ Income in Pandemic Covid-19 Period - Habsari, Aulia; Yuliawati, Yuliawati (JURNAL MANAJEMEN AGRIBISNIS; Vol 11 No 01 (2023): Jurnal Managemen AgribisnisDO - 10.24843/JMA.2023.v11.i01.p03, 2023)
In the early days of Covid-19, the Stay at Home policy made the demand for mustard mustard greens, so the selling price of mustard greens plummeted. Mustard greens farmers in Ngipik Hamlet are also constrained to organize farmer group associations, counseling, to carry out traditional events, so that social capital is not maximized, and the losses of mustard greens farmers in the early days of the Covid-19 pandemic cannot be minimized. This study aims to determine the level of social capital and social capital relationships (norms, networks, and trust) of mustard greens farmers in Ngipik Hamlet, Candi Village, Bandungan District, Semarang Regency at the beginning of the Covid-19 pandemic. This research was conducted in September 2020. The sample of this research is 40 mustard greens farmers in the Pemuda Tani farmer group and Mitra Subur Rejeki farmer group with a minimum area of ??land cultivated which is 500m2. Data obtained through interviews with questionnaires. Data analysis with Spearman rank correlation analysis. The results of this study are that the level of social capital elements of farmers is low to medium, and there is a relationship between social capital norms, networks, and farmer trust with a very strong relationship and a positive direction of relationship with income, so it is recommended to strengthen social capital.